RESPONSE SURFACE METHODOLOGY FOR OPTIMIZATION OF PRODUCTION OF MEVASTATIN BY SOLID STATE FERMENTATION USING SESAME OIL CAKE - N. HARSHA; V. SRIDEVI; M.V.V. CHANDANA LAKSHMI; K.VIJAY KUMAR (International Journal of Pharma and Bio Sciences, 2013)
Mevastatin, also known as compactin or ML-236B is a member of the class of statins belonging to the polyketide group. Polyketides are rich sources of pharmaceuticals, including antibiotics, anticancer drugs, and cholesterol-lowering drugs, immunosuppressants and other therapeutics [1]. This study was performed for the production of mevastatin using sesame oil cake as substrate with Pencillium citrinum MTCC 1256 by Solid State FermentationThe present study was carriemevastatin by solid state fermentation with Pencillium citrinum MTCC 1256 using sesame oil cake. Different agro residues as substrates and different organisms were screened and various physico-chemical parameters were optimized. In this paper we explained in detail on the four significant factors i.e, fermentation time (X1, days), temperature (X2,oC), pH (X3), nitrogen source (X4,%w/v), which significantly influence the production of mevastatin were selected by using Plackett-Burman statistical design. These variables were further optimized using a 24 full factorial CCD (Central Composite Design) and a second order polynomial model equation was obtained. In the present study the value of the regression coefficient R2 = 0.9938 which indicates that 99.38% of the variability in the response could be explained by the model. The adjusted R2 value is 0.9859 which is also very high to advocate the significance of the model.